THE INFLUENCE OF SYARIAH BUSINESS PRODUCT QUALITY IN INCREASING COMPANY SALES VOLUME - Yuni Mayanti; Jujun Jamaludin; Putri Zafira Ruhliandini; Diki Ahmad; Yasir Muharram Fauzi (UIN Sunan Gunung Djati Bandung, 2025)
This study aims to analyze the effect of product quality in sharia business on increasing the company's sales volume. This study uses a library research method, namely by reviewing various sources of literature such as books, scientific journals, articles, and research reports that are relevant to the topic. Through a descriptive qualitative approach, this study examines various theories and previous findings related to product quality management, quality improvement strategies, and consumer behavior in the context of sharia business. The results of the study indicate that product quality has a central role in shaping positive consumer perceptions of the brand and sharia values ​​carried by the company. Consumers who are satisfied with product quality tend to have high loyalty and make repeat purchases, and recommend the product to others. In addition, the application of sharia principles such as honesty, transparency, and social responsibility in the production and marketing processes also strengthens the company's positive image in the eyes of the public. The strategy of improving product quality that is carried out continuously is the main key to expanding the market and increasing sales volume. Thus, the results of this study are expected to be a reference for sharia business actors to focus more on quality as the main foundation in achieving competitive and sustainable growth.